The different structure-function correlation as measured by OCT and octopus perimetry cluster analysis in intracranial tumor and glaucoma patients - Li, Xiaochun; Qin, Jiayin; Cao, Xiaoguang; Ren, Zeqin; Cui, Ting; Bao, Yongzhen (Frontiers in Endocrinology, 2022)
Background To explore the correlation of visual field (VF) defect values and retinal nerve fiber layer (RNFL) thickness for the intracranial tumor and glaucoma patients. Methods Retrospective analysis is performed for the intracranial and glaucoma patients, whose VF defect values measured with Octopus perimeter cluster analysis, and RNFL thickness, ganglion cell layer (GCL) thickness and optic disk parameters measured with swept source OCT. The differences between VF and RNFL (included the data of optic disc) are calculated. The correlation between VF defect values and RNFL, GCL thickness are explored. Results 43 eyes of 29 patients with intracranial tumor and 31 eyes of 19 patients with glaucoma are enrolled. Thickness of RNFL not only for the whole (360°), but also for the four quadrants are thinner in the glaucoma group than those of the intracranial tumor group (p<0.05), and similar for the thickness of GCL without significance (p﹥0.05). There is no significant difference of VF for those two groups except the glaucoma has lower sLV (p<0.05). Stronger correlation for mean deviations (MD)s of VF ten clusters and RNFL thickness of OCT twelve sectors is found in the glaucoma patients, but few in the intracranial tumor patients. Logistic regression also shows the loss of RNFL or increasing of vertical CDR and cup volume tending to the diagnosis of glaucoma and the irregular VF damage is inclined to the diagnosis of intracranial tumor. Conclusions Intracranial tumor has a weak correlation between the RNFL thickness and Octopus VF MD, compared with that of glaucoma. OCT and Octopus VF might provide more helpful information for the differential diagnosis of intracranial tumor and glaucoma.